Optimasi Desain Ban Tanpa Udara (Non Pneumatic Tire) Dengan Struktur Hexagonal Honeycombs Menggunakan Response Surface Method (RSM) - Farit Hendro Wibowo; Moch. Agus Choiron; Anindito Purnowidodo (UM Purwokerto Press, 2021)
Non-Pneumatic Tires (NPT) are tires that do not use compressed air like other tires. In this paper, the optimal design obtained is based on the static and explicit dynamic behavior of the NPT construction, which has hexagonal honeycomb spokes. The hexagonal honeycomb type NPT component consists of the hub wheel, outer ring, spokes, and tread. The honeycomb model is made differently based on tread thickness (20 mm, 25 mm, 30 mm), outer ring thickness (0.25 mm, 0.5 mm, 0.75 mm), spokes thickness (3 mm, 5 mm, 7 mm), and the number of spokes holes (12, 13, 14). Based on the simulation results of Ansys and Minitab, the recommended optimal design is 20 mm tread thickness, 3.2 mm spokes thickness, 0.25 mm outer thickness, and the number of holes 12 pieces.